Windows Essential Business Server 2008 : administrator's companion - Mackin, J. C. (Microsoft Press, 2009)
Get your midsize IT infrastructure up and running smoothly. This indispensable, single-volume reference details the features and capabilities of Windows Essential Business Server 2008. Gain the real-world insights, practical workarounds, and key troubleshooting tactics you need for on-the-job results. Discover how to: Plan, install, and configure Windows Essential Business Server 2008Use the Administration Console interface to manage the networkConfigure user settings with Group Policy, scripts, user profiles, and Folder Redirection<li.